Health Technology Assessment of Public Health Interventions Published 2012 to 2016: An Analysis of Characteristics and Comparison of Methods. (24th July 2019) - Polus, Stephanie; Mathes, Tim; Klingler, Corinna; Messer, Melanie; Gerhardus, Ansgar; Stegbauer, Constance; Willms, Gerald; Ehrenreich, Heidi; Marckmann, Georg; Pieper, Dawid
Abstract: Objectives: The aim of this study was to provide an overview of the methodological characteristics and compare the assessment methods applied in health technology assessments (HTAs) of public health interventions (PHIs). Methods: We defined a PHI as a population-based intervention on health promotion or for primary prevention of chronic or nonchronic diseases. HTAs on PHIs were identified by systematically searching the Web pages of members of international HTA networks. We included only full HTA reports published between 2012 and 2016. Two reviewers extracted data on the methods used to assess effectiveness/safety, as well as on economic, social, cultural, ethical, and legal aspects using a-priori standardized tables. Results: We included ten HTAs provided by four different organizations. Of these, all reports assessed the effectiveness of the interventions and conducted economic evaluations, seven investigated social/cultural aspects, and four each considered legal and ethical aspects, respectively. Some reports addressed applicability, context/setting, and intervention fidelity issues in different ways. We found that most HTAs adapted their methods to some extent, for example, by including nonrandomized studies, expanding the search strategy, involving stakeholders, or applying a framework to guide the HTA process. Conclusions: Our analysis provides a comprehensive overview of methods applied in HTAs on public health interventions. We found that a heterogeneous set of approaches is used to deal with the challenges of evaluating complex public health interventions.